2021
DOI: 10.1111/btp.12943
|View full text |Cite
|
Sign up to set email alerts
|

Shade alters the growth and architecture of tropical grasses by reducing root biomass

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…This phenomenon was reflected in a DM (Gusmão et al, 2020). Solofondranohatra et al (2021) reported that, when plants reach their optimal leaf area index, the shadow on the lower layers of the canopy increases and senescence is higher than the growth of the leaves. Meanwhile, a high forage production and a low accumulation of dead material can be obtained, when 95% of the radiation is intercepted during the vegetative stage (Niinemets, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This phenomenon was reflected in a DM (Gusmão et al, 2020). Solofondranohatra et al (2021) reported that, when plants reach their optimal leaf area index, the shadow on the lower layers of the canopy increases and senescence is higher than the growth of the leaves. Meanwhile, a high forage production and a low accumulation of dead material can be obtained, when 95% of the radiation is intercepted during the vegetative stage (Niinemets, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This inherent trait underscores the species' pro ciency for sustained survival over an extended period within the canopy's shaded environment. Alternatively, grasses with lower shade adaptation (classi ed as shade avoiders) exhibit increased partitioning preferentially to shoot at the expense of root biomass when exposed to low light environments (Solofondranohatra et al 2021). In naturally dense communities, shoot elongation induced by low red/far-red light may confer a tness advantage, enabling shade-avoiding grasses to adjust their growth patterns, optimize their exposure to sunlight, and rapidly dominate gaps in the canopy (Pierik et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although the low R:S ratio can be associated to the 50% shade in the nursery, increasing biomass allocation to shoot (Solofondranohatra et al 2021) can result in plants less resilient to fire and drought, once the lower belowground biomass can negatively affect resprouting and water uptake capacities, as well as larger shoots would increase plant transpiration (Giles et al 2021;Solofondranohatra et al 2021). However, despite the decreasing R:S ratio, there was an increase on root biomass with higher CRF rates, which can promote higher belowground carbon storage, nutrient cycling efficiency and erosion resistance (Bardgett et al 2014).…”
Section: Discussionmentioning
confidence: 99%